The Rise and Fall of the East India Company : A Sociological Appraisal - Mukherjee, Ramkrishna (Lahore People's Publishing House, 1976)
Looking for something great to read? Browse our editors' picks for the best books of the year in fiction, nonfiction, mysteries, children's books, and much more.
Include Notes, References and Index
Keywords: East India Company -- History -- East India Company -- Historia Da Asia